2002
DOI: 10.1016/s0039-9140(02)00056-5
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the acidity and the complexing ability of (o-hydroxyphenyl) bis- and (o-hydroxyphenyl) mono-methylenephosphonic acids towards lanthanide(III) ions

Abstract: The characterization of the acid-base properties of a family of three phenoldimethylenephosphonic acids differently substituted by auxo-or chromophoric groups was studied. These ligands may be considered as pentaacids. Their pK a were determined in aqueous solution at 25°C and constant ionic strength 0.1 mol dm − 3 by potentiometry and UV-visible spectrophotometry. Eventually, the complexing power of these molecules with lanthanide cations, Ce 3 + , Pr 3 + , Nd 3 + , Sm 3 + and Eu 3 + , was studied keeping in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…In all cases, the values of log β 11z diminish when passing from log β 111 to log β 115 . This fact was already observed and explained on the basis of charge effect [29,36]. The hydrolysis constants log β 11−1 for Fe(III) complexes are −0.53, −0.50, and −0.85 for L1, L2, and L3, respectively.…”
Section: Study Of the Complexation Of Metal Cations Fe(iii) Complexessupporting
confidence: 61%
See 1 more Smart Citation
“…In all cases, the values of log β 11z diminish when passing from log β 111 to log β 115 . This fact was already observed and explained on the basis of charge effect [29,36]. The hydrolysis constants log β 11−1 for Fe(III) complexes are −0.53, −0.50, and −0.85 for L1, L2, and L3, respectively.…”
Section: Study Of the Complexation Of Metal Cations Fe(iii) Complexessupporting
confidence: 61%
“…More recently, the study of intramolecular stacking interactions in ternary Cu(II) complexes formed with an heteroaromatic amine and 9-[2-(2-phosphonoethoxy)ethyl]adenine was published [24]. Chafaa et al [25,26] have reported the acidbase properties of a series of (o-hydroxyphenyl) methylenephosphonic acids synthesized by Vogt et al The stability constants of the complexes obtained from these ligands and bivalent transition metals cations [27,28] and a wide variety of lanthanide(III) cations and thorium(IV) were determined [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…This is necessary in order to determine the hydrolysis constants that are to be injected as fixed values for the calculation of the stability constants of the complexes of lanthanides (III) and of thorium (IV) cations with (phenolic) monoand dimethylenephosphonic acids [17,18] synthesised by Böhmer et al [19]. The treatment by Sirko-P [20] and Superquad [21] of the different titration curves corresponding to different lanthanides permitted the interpretation of this increase of H + ions concentration by the following hydrolysis equilibriums:…”
Section: Hydrolysis Of Lanthanides (Iii) and Of Thorium (Iv)mentioning
confidence: 99%
“…The titrating agent NaOH (1 or 0.1 mol dm -3 ) used was stored in a polyethylene container equipped with a CO 2 trap. All experiments were performed according to the method previously described [18].…”
Section: Potentiometric Measurementsmentioning
confidence: 99%
“…15 Organo-phosphonic acids have been used as complexing agents due to their strong binding ability and the stability of the complexed species. [15][16][17][18][19][20][21][22] Recently calix [4]resorcinolarenes with phosphinoylalkyl substituents with acidic phosphonate fragments were shown to be efficient extracting agents of the metal ions of the lanthanum group from acidic solutions. 23,24 Structurally related derivatives, calix [4]arene methylenebisphosphonic acids, also displayed strong inhibition of calf intestine alkaline phosphatase.…”
Section: Introductionmentioning
confidence: 99%